Saudi Arabia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper assesses the importance of oil and interest rate spillovers for Saudi Arabia. Oil prices have fallen by more than 40 percent since mid-2014 while the Federal Reserve is expected in the coming months to begin raising its policy rate at the beginning of a gradual tightening cycle. Given the importance of oil to the economy and the peg of the riyal to the U.S. dollar, these are two key developments for Saudi Arabia. Although a temporary drop in oil prices would likely have little effect on the economy and banks given the financial cushions that have been built-up, a longer-lasting period of low oil prices would have a more significant impact.